2023
DOI: 10.52312/jdrs.2023.1012
|View full text |Cite
|
Sign up to set email alerts
|

Can pirfenidone prevent tendon adhesions? An experimental study in rats

Tülin Türközü,
Necip Güven,
Fikret Altindağ
et al.

Abstract: Objectives In this experimental study, we aimed to investigate the effectiveness of oral pirfenidone (PFD) treatment on preventing tendon adhesion and tendon healing in rats. Materials and methods A total of 21 rats were assigned into three groups including seven rats in each group. In Group 1 (sham group), no surgical procedure was performed. In Group 2 (control group), tendon repair was performed following right achillotomy. In Group 3 (treatment group), the rats also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…In a study, pirfenidone, a drug with antifibrotic and anti-inflammatory properties currently used in the treatment of idiopathic pulmonary fibrosis, was utilized to prevent tendon adhesion and tendon healing in rats with Achilles tendon damage. [ 26 ] The results indicated that pirfenidone decreased collagen synthesis and prevented the formation of peritendinous adhesion in rats; however, it did not impair tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, pirfenidone, a drug with antifibrotic and anti-inflammatory properties currently used in the treatment of idiopathic pulmonary fibrosis, was utilized to prevent tendon adhesion and tendon healing in rats with Achilles tendon damage. [ 26 ] The results indicated that pirfenidone decreased collagen synthesis and prevented the formation of peritendinous adhesion in rats; however, it did not impair tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Many reasons such as slow regeneration rate, low blood perfusion, and inability to use the implants used in the fixation of bone fractures for these tissues cause the healing process of injured tendons to prolong with respect to other tissues. [4] Studies are continuing on the effects of various antioxidant or anti-inflammatory substances in this difficult and long healing process of tendons. [5,6] Caffeic acid is one of the phenolic compounds synthesized by plants and commonly found in nature and in the human diet.…”
mentioning
confidence: 99%